Tanggungjawab Korporasi Terhadap Tindak Pidana Yang Dilakukan Pegawai: (Kasus Alat Tes Rapid Menggunakan Antigen Daur Ulang) - Hartanto, (Yuriska: Jurnal Ilmiah Hukum, 2021)
Background: In the government's efforts to control the spread of the Covid-19 virus, news broke about employees of a corporation using used (recycled) antigens at Kualanamu Airport in Medan. Some people who incidentally are health workers from BUMN abuse their circumstances/authority to the detriment of society and endanger the lives of patients/consumers. This health worker who is an employee of this BUMN has committed a crime, then this act that harms the public is quite broad, indirectly/indirectly related to corporate responsibility (BUMN). Research Methods: This writing uses a statutory approach related to the case of recycling antigen devices. This type of normative legal research examines library materials or secondary data and tertiary legal materials. Secondary data consists of legal materials in the form of journals, scientific documents and expert opinions. This is a juridical-normative research that examines the application of positive legal norms, to seek the truth of coherence, namely whether the rule of law is in accordance with legal norms and legal principles, then also conducts problem solving to provide prescriptions, or descriptions of the formulation of the problem. The laws and regulations used as analysis are Law 40 of 2007 concerning Limited Liability Companies, Perma Number 13 of 2016, the Constitutional Court Decision Number 62/PUU-XI/2013, and the Criminal Code. Findings: Jurisprudence in Indonesia is not necessarily the actions of branch employees of PT. Kimia Farma Diagnostics can be related to the responsibility of the directors/corporations, as long as there is no evidence of negligence from the board of directors for this criminal act, or the negligence of the board of directors in supervising the head of the branch. Conclusion: Criminal acts committed by the perpetrators can be subject to several criminal sanctions in the field of health or consumer protection, but linking them to corporations (BUMN) requires further proof of elements.